2013
DOI: 10.3121/cmr.2013.1160
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Risk in Pre-Diabetic Men: A Matched Cohort Study

Abstract: Background: Diagnosis and duration of type 2 diabetes mellitus (DM) appear to be associated with decreased prostate cancer risk. Limitations of previous studies include methods of subject selection and accurate definition of DM diagnosis. We examined the temporal relationship between DM and prostate cancer risk exploring the period of greatest risk starting from the prediabetic to the postdiabetic period using clinical and administrative data to accurately define the date of DM diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…The risk for developing prostate cancer declined briefly after the onset of diabetes mellitus and this reduction continued for the following 15 years. This declining risk might be caused by a drop in testosterone levels 112 . Considering the ample evidence associating diabetes with cancer, it is clear that more investigations are needed to clarify the mechanism by which diabetes can cause or, in some circumstances, even prevent cancer.…”
Section: Systemic Metabolic Diseases With Possible Influence On Tumormentioning
confidence: 99%
“…The risk for developing prostate cancer declined briefly after the onset of diabetes mellitus and this reduction continued for the following 15 years. This declining risk might be caused by a drop in testosterone levels 112 . Considering the ample evidence associating diabetes with cancer, it is clear that more investigations are needed to clarify the mechanism by which diabetes can cause or, in some circumstances, even prevent cancer.…”
Section: Systemic Metabolic Diseases With Possible Influence On Tumormentioning
confidence: 99%
“…Considering results of cohort studies published between 2007 and 2017, eight studies did not identify a significant impact of smoking status or habits on PCa risk [10][11][12][13][14][15][16][17], while another 10 studies showed an inverse association of smoking with reduced PCa risk [18][19][20][21][22][23][24][25][26][27]. On the contrary, when reviewing case-control studies (CCSs), only two studies did not find an impact on PCa incidence [28,29]: a study from Argentina found the same proportion of smokers in patients with PCa and controls [28]; also, May et al [20] did not find significant differences in the rate of advanced tumor stages between smokers and nonsmokers, while overall PCa risk was not evaluated.…”
Section: Smoking and Risk For Pcamentioning
confidence: 99%
“…Exclusion reasons are provided in Supplementary Table S1. Thirteen articles [28][29][30][32][33][34][35][36][37][38][39][40][41] , including 3,345,031 patients with T2D with age ranging from 18 to 90 year fulfilled our inclusion criteria. Detailed characteristics of the studies included in the present meta-analysis are shown in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Although the associations between BMI and the risk of total and site-specific cancers in the general population have been widely investigated 3,[9][10][11][12]15,26 , such associations in patients with existing type 2 diabetes have been less investigated and results are less clear than in general population-based studies [27][28][29][30][31][32] . Some studies have found a positive association with risk of total cancer [31][32][33] , however, not all studies have been consistent 29,30,34,35 , and results have been less convincing for hormone-related [27][28][29][30]32,[36][37][38] and colorectal cancer 29,30,32 .…”
mentioning
confidence: 99%